Do Bamboo Dancing Technique Affect the Students’ Speaking Ability? - Pitanto, Jeri (English Education:Journal of English Teaching and Research, 2016)
The problems of this research were to know the students’ speaking ability before and after they taught by use bamboo dancing technique. This experimental research was conducted at the XI IPS 3, consists of 28 students, eleventh grade at SMAN 1 GondangNganjuk in academic year 2014/2015. The research data were collected using pre test and post test. The research results showed that the students’ score of pre test is 1576. The mean of students score of pre test is 56.28 and the students’ speaking ability after taught by using bamboo dancing technique is better more than before taught. Because the students’ score in post test is 2292 and the mean of students’ score in post test is 81.85. It can be said that the students’ score is increasing after they are taught by using bamboo dancing technique in teaching speaking. The t-score computation showed that the t-score is 19.196 at degree of freedom 27 and t-table is 2,771 at the level of significance 1% and 2,052 at the level of significance 5%. It means that t-score (19,196) > t-table at the level of significance 1% (2,771) and t-score (19,196) < t-table at the level of significant 5% (2,052). So the t-score is higher than t-table in significance 1% and 5%. Therefore, the alternative hypothesis (Ha) is accepted and null hypothesis is rejected. It can be concluded that teaching speaking using bamboo dancing technique has significant effect to the student’s speaking ability